Strengthening Digital Literacy in Online Time Management among Senior High School Students - Ibad, M. Nashoihul; Saelaemae, Tasnim (LPPM STAI Darul Falah, 2024)
Rapid advances in digital technology have made digital literacy an important skill, especially among senior high school students who spend much time online. This community service project aims to improve digital literacy and time management skills among senior high school students, with a focus on effective and productive online activities. This project was carried out in collaboration with Gontangwetan Pasuruan Public High School 1 which involved students as the main beneficiaries. A participatory approach be used, including pre-assesment and post-assessment, interactive workshops, and ongoing mentoring. The findings showed a significant improvement in students' understanding of digital literacy, with an average increase of 25% in digital literacy and online time management skills. This increase results in better academic performance and a more balanced lifestyle. The results underscore the importance of equipping students with digital literacy skills to navigate the digital age effectively. This community service project demonstrates the potential of the initiative to foster responsible digital behavior and improve overall student productivity.